Pengaruh Kualitas Produk, Harga dan Word Of Mouth Terhadap Keputusan Pembelian Pada CV Pramita Kediri - Dwi Khoirunnisa A; Eko Widodo; Diana Ambarwati (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This research aims to determine the influence of product quality, price and word of mouth on purchasing decisions at CV Pramita Kediri. This type of research is quantitative research. This research data was obtained through primary and secondary data. The population in this research are consumers at CV Pramita Kediri. The sample in this research was 384 consumers with a sampling technique using the Slovin formula. The analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that the partial t test results show that the variables product quality, price and word of mouth influence purchasing decisions at CV Pramita Kediri. The results of the F test simultaneously mean product quality, price and word of mouth influence purchasing decisions at CV Pramita Kediri.